ANALISIS EFEKTIFITAS SOSIAL MEDIA TIKTOK DI LORONG TEMU COFFEE BOGOR - Maria Paulina Manik; Aggy Lestari Dwi Putri (Bogor Hospitality Journal, 2026)
Currently, social media has significantly evolved. What was once merely a tool for communication has now become much more advanced. We can upload videos and photos, and even generate income through social media. One of the most widely used social media platforms is TikTok. It is not only used by individuals but also extensively utilized by business owners to promote and grow their businesses. This study aims to examine the effectiveness of using TikTok as a social media platform for Lorong Temu Coffee in Bogor. The population in this research consists of followers of Lorong Temu Coffee Bogor’s TikTok account. The research method employed is quantitative, involving the calculation of the mean, median, mode, and standard deviation. Data collection was conducted through questionnaires distributed to 50 respondents. Based on the data analysis, it can be concluded that the effectiveness of TikTok social media for Lorong Temu Coffee Bogor measured across four dimensions of effectiveness resulted in the following scores: Context received 209, Communication received 197, Collaboration received 209, and Connection received 210. The overall average score was 206, which falls between “agree” and “strongly agree” on the scale. This indicates that TikTok has been fairly effective as a marketing platform for Lorong Temu Coffee Bogor. Nonetheless, further efforts are still needed to enhance this effectiveness, especially in terms of user interaction. It is recommended that Lorong Temu Coffee Bogor actively encourage follower engagement on TikTok through activities such as Q&A sessions and collaborative content.